2000
DOI: 10.1016/s0021-9673(00)00808-6
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric and diastereomeric high-performance liquid chromatographic separation of cyclic β-substituted α-amino acids on a copper(II)-d-penicillamine chiral stationary phase

Abstract: High-performance liquid chromatographic (HPLC) separation of stereoisomeric cyclic beta-substituted alpha-quaternary alpha-amino acids was performed by ligand-exchange on a copper(II)-D-penicillamine chiral stationary phase. The investigated amino acids are the 1-amino-2-methylcyclohexanecarboxylic acids, the 1-amino-2-hydroxycyclohexanecarboxylic acids, the 1-amino-2-methylcyclopentanecarboxylic acids and the trans-configured 1,2-diaminocyclohexanecarboxylic acids. The effects of the mobile phase composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…R-SBC hydrophobically binds to the RP-18 solid support, thus producing a stable, dynamically coated chiral stationary phase. The presence of a sulfur atom in the amino acid side chain of the selector covalently 19 or hydrophobically bound 5,20,21 to the solid support has been already reported. The chiral selector in the coated phase was N,Sdioctyl-D-penicillamine, which binds to the C-18 carbon chains through both the C-8 alkyl substituents.…”
Section: Introductionmentioning
confidence: 84%
“…R-SBC hydrophobically binds to the RP-18 solid support, thus producing a stable, dynamically coated chiral stationary phase. The presence of a sulfur atom in the amino acid side chain of the selector covalently 19 or hydrophobically bound 5,20,21 to the solid support has been already reported. The chiral selector in the coated phase was N,Sdioctyl-D-penicillamine, which binds to the C-18 carbon chains through both the C-8 alkyl substituents.…”
Section: Introductionmentioning
confidence: 84%
“…Chiral ligand exchange stationary phase prepared by embedding Cu (II)-N,S-dioctyl-D-penicillamine in a reversed-phase C 18 silica gel as reported by Oi et al (1995) was employed for resolution of enantiomers and diastereomers of cyclic b-substituted a-quaternary a-amino acids (Schlauch et al, 2000). The developed method proved to be successful for resolution of all the stereoisomers under study except for the two diastereomers of 1-amino-2-methylcyclopentanecarboxylic acid.…”
Section: Application Of Pena As Chiral Selector As Cdrmentioning
confidence: 99%
“…Several chiral ligand-exchange stationary phases have been applied so far with different chiral selectors, e.g., proline, 5,7 leucinol derivative, 13 norephedrine, 8 and penicillamine. 9,11 Applying copper(II) as the metal ion, the formation of a five-member chelate ring is normally expected and a square planar structure is usually proposed for the ternary complexes involving Cu(II) and chelating ligands. 7,8,12 Penicillamine theoretically may interact via its N-, O-, and S-atom acting as a tridentate ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al 14 used penicillamine as chiral ligand for ligand-exchange micellar electrokinetic chromatography and suggested that the pencillamine acts as a bidentate chelate, coordinating with Cu(II) via the amino nitrogen and the carboxyl oxygen (the -SH group does not participate in the chiral recognition process). Schlauch et al 11 proposed that penicillamine forms a bidentate complex via its N-, O-, or S-atoms and found that the acetonitrile content in the mobile phase has a crucial role in the discrimination of b-substituted a-amino acids.…”
Section: Introductionmentioning
confidence: 99%